2017
DOI: 10.1136/bmj.j448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of searching clinical trial registries in systematic reviews of pharmaceutical treatments: methodological systematic review and reanalysis of meta-analyses

Abstract: Objective To evaluate the impact of searching clinical trial registries in systematic reviews. Design Methodological systematic review and reanalyses of meta-analyses. Data sources Medline was searched to identify systematic reviews of randomised controlled trials (RCTs) assessing pharmaceutical treatments published between June 2014 and January 2015. For all systematic reviews that did not report a trial registry search but reported the information to perform it, the World Health Organization International Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 38 publications
2
79
0
Order By: Relevance
“…Trial registries (eg, ClinicalTrials.gov) are useful for identifying trials, comparing published results with planned outcomes and methods and obtaining results not reported elsewhere . Registries may also include data about potential harms that cannot be obtained through other sources .…”
Section: Step 1 Specify Which Sources You Will Use For Your Review Amentioning
confidence: 99%
“…Trial registries (eg, ClinicalTrials.gov) are useful for identifying trials, comparing published results with planned outcomes and methods and obtaining results not reported elsewhere . Registries may also include data about potential harms that cannot be obtained through other sources .…”
Section: Step 1 Specify Which Sources You Will Use For Your Review Amentioning
confidence: 99%
“…Although ignored during publication, negative studies assume just as much importance as published ones when the aim is to summarize evidence on a topic of interest. Importantly, including results from unpublished studies has been shown to alter the results of meta-analysis [12,13]. Thus, searching unpublished research is important for valid meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search for data from a diverse body of evidence is fundamental to serve that purpose. In addition to extracting data from published studies, it is important to search unpublished studies (also known as gray literature) as research shows that the latter have smaller treatment effects than published studies [10,11] and that inclusion of unpublished results can change conclusions of meta-analyses [12,13]. Conversely, failure to include unpublished data biases the results toward a positive treatment effect (also known as publication bias) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the impact of searching trials registers, Baudard et al analysed 223 systematic reviews. One hundred and sixteen reviews (52%) did not report having searched trials registers.…”
Section: Discrepancies Between Unpublished Data and Trial Protocols mentioning
confidence: 99%